The effects of corporate rebranding on customer satisfaction and loyalty: Empirical evidence from the Ghanaian banking industry - Bylon Abeeku Bamfo; Courage Simon Kofi Dogbe; Charles Osei-Wusu (Cogent Business & Management, 2018)
The study examined whether or not the rebranding activities in the Ghanaian banking industry, had any influence on customers' perception on service quality, their level of satisfaction and their level of loyalty. These relationships were ascertained by running a moderation and linear regression analyses. The study identified that, rebranding had no statistically significant effect on perceived service quality, customer satisfaction and customer loyalty, in the Ghanaian banking industry. Rebranding had no moderating effect on the relationship between service quality and customer satisfaction. It also had no moderating effect on the relationship between service quality and customer loyalty. And finally, rebranding did not have a moderating effect on the relationship between customer satisfaction and customer loyalty. It was concluded that, rebranding activities in the Ghanaian banking industry had no significant effect on customers' attitude towards the brand. Banks and other financial institutions must therefore be circumspect when it comes to investment in rebranding activities and be more interested in making investments that will positively influence the attitude of their customers.
Keywords: 650